Molecular phylogenetics of sub-Saharan African natricine snakes, and the biogeographic origins of the Seychelles endemic Lycognathophis seychellensis - Deepak, V; Maddock, Simon T; Williams, Rhiannon; Nagy, Zoltán T; Conradie, Werner; Rocha, Sara; James Harris, D; Perera, Ana; Gvoždík, Václav; Doherty-Bone, Thomas M; Kamei, Rachunliu G; Menegon, Michele; et al. (Molecular phylogenetics and evolution, 2021)
Phylogenetic relationships of sub-Saharan African natricine snakes are understudied and poorly understood, which in turn has precluded analyses of the historical biogeography of the Seychelles endemic Lycognathophis seychellensis. We inferred the phylogenetic relationships of Seychelles and mainland sub-Saharan natricines by analysing a multilocus DNA sequence dataset for three mitochondrial (mt) and four nuclear (nu) genes. The mainland sub-Saharan natricines and L. seychellensis comprise a well-supported clade. Two maximally supported sets of relationships within this clade are (Limnophis,Natriciteres) and (Afronatrix,(Hydraethiops,Helophis)). The relationships of L. seychellensis with respect to these two lineages are not clearly resolved by analysing concatenated mt and nu data. Analysed separately, nu data best support a sister relationship of L. seychellensis with (Afronatrix,(Hydraethiops,Helophis)) and mt data best support a sister relationship with all mainland sub-Saharan natricines. Methods designed to cope with incomplete lineage sorting strongly favour the former hypothesis. Genetic variation among up to 33 L. seychellensis from five Seychelles islands is low. Fossil calibrated divergence time estimates support an overseas dispersal of the L. seychellensis lineage to the Seychelles from mainland Africa ca. 43-25 million years before present (Ma), rather than this taxon being a Gondwanan relic.
Keywords: Natricidae; Natricinae; Seychely; Biogeography; fylogeografie; molekulární evoluce; subsaharská Afrika; Gondwana; Phylogeny; Sequence Analysis, DNA; Systematics; Overseas dispersal; fylogeneze; Colubridae; Animals; Evolution, Molecular; sekvenční analýza DNA; Seychelles; zvířata; Africa South of the Sahara; Phylogeography